Restrukturisasi Badan Usaha Milik Negara Perbankan Melalui Pembentukan Holding Company Di Indonesia - Agus Prasetiyo (Lex Renaissance, 2019)
The purpose of the study is to analyze the aspects, strengths and weaknesses in restructuring State-Owned Banks (BUMN Banks) through the establishment of a holding company in Indonesia. This is a normative legal research with the regulatory approach. The method used in the data collection is by collecting the legals materials and the study of documents. The analysis of legal materials uses the descriptive-qualitative (juridical-normative) approach. Conclusion of the results of the study: First, aspects that need to be considered in the establishment of a BUMN holding company include legal (juridical) and non-legal aspects such as economics and so on. Second, there are more advantages compared to weaknesses in the establishment of a BUMN holding company. This effort is an alternative choice or step to form a strong financial and banking institution in the ASEAN region